Potential for the use of chemical properties as indicators of soil quality. A review - Gutiérrez D., Joan Sebastián; Cardona, William Andrés; Monsalve C., Oscar Iván (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The need to understand and evaluate the quality of soils in agricultural production systems is an issue of increasing importance today because of the determination of impacts from management practices on the sustainability of this resource. The objective of this review is to provide an overview of the concept of soil quality and indicators for its evaluation and to present some research on the potential of chemical properties for use as indicators of soil quality. Among the chemical properties that can be considered as indicators are nutrient availability, organic carbon content and labile organic carbon, pH, phosphate binding capacity, electrical conductivity, cation exchange capacity, total nitrogen and mineralizable and organic matter. The importance of multivariate techniques to define chemical properties with a potential as soil quality indicators is highlighted. The greatest concern for the sustainable use of soil resources includes the need to develop approaches and tools that generate diagnoses for the effects of management practices implemented in the systems of agricultural production, that is, to provide information about soil quality in a given context.